High-voltage CMOS active pixel sensor chip with counting electronics for beam monitoring - Weber, Alena; Ehrler, Felix; Schimassek, Rudolf; Perić, Ivan (IEEE transactions on nuclear science, 2022)
This article presents the monolithic active high-voltage CMOS (HV-CMOS) pixel sensor HitPix with counting electronics and frame-based readout. It has been developed for high rate ion-beam monitoring, as used, e.g., in medical facilities for radiation therapy. The sensor elements are lowly doped n-well in p-substrate diodes. Pixel electronics is implemented within the sensor cathode (n-well). The substrate can be biased to −120 V. In this way, a large depletion zone is induced and radiation tolerance is improved. We could show the overall functionality of the sensor by laboratory measurements of the signal response characteristics and threshold distribution. Furthermore, testing the sensor in the medical ion beam of Heidelberg Ion-Beam Therapy Center (HIT) has proven the suitability of this beam monitor approach.
Gesehen am 29.07.2022